O contexto da pandemia da Covid-19 e a transição do ensino remoto para o presencial : um estudo com profissionais de escolas da rede pública de educação - Lacerda, Rebbeca Hellen Araújo (2023)
This dissertation addresses the performance of teachers and school psychologists from the municipal public network of João Pessoa-PB during the COVID-19 pandemic. The COVID-19 pandemic presented itself as a crisis in Brazil and in the world, causing social distancing and the consequent closure of school institutions, having a clear impact on the continuity of early childhood education. In this sense, the objective is to investigate and analyze practices of teachers and psychologists during the COVID-19 pandemic, and to map actions regarding the transition from remote teaching to blended and face-to-face teaching. This question was initially explored through the explanation of the cultural-historical theoretical framework and contemporary arguments about development transitions. Within the scope of the study, the theme of the COVID-19 pandemic was presented and discussed, and its implications for the school context, and a bibliographical survey was described on the professional practices of School Psychology during the pandemic. A qualitative field research was carried out, with a semi-structured interview applied to 22 participants, 11 teachers and 11 school psychologists from municipal schools in João Pessoa. The sociodemographic results indicate that most psychology professionals had an internship in the clinical area, and that most psychologists completed their graduation in public educational institutions and before the 2000s. The results of the analyzes of the interviews with the teachers indicate pedagogical demands generated during the pandemic, caused by the lack of access to technology or the lack of presence in the online classroom by students, difficulty in handling technology to create content for students or even doubts about what this return to face-to-face would look like. However, they also reveal practical reformulations to deal more adequately with the return to the physical space of institutions. In the interviews with the psychologists, actions aimed mainly at teachers, technicians, students and families were identified. These professionals perceived this return to the classroom as an ongoing readaptation, at the same time referring to the school space of power, readaptations and guarantee of rights. This research reaffirms the role of the school psychologist as a professional who can promote understanding of the reality and complexity of events related to the pandemic, as well as adapt the pedagogical team to a new practice and actions that value active and collective construction.